PEMANFAATAN LIMBAH KULIT PISANG ABU (Musa paradisiaca L) SEBAGAI SEDIAAN GEL ANTIOKSIDAN ALAMI - Indrayani, Ferna; Wirastuty, Reski Yalatri (MEDFARM: Jurnal Farmasi dan Kesehatan, 2024)
Antioxidants are substances that inhibit or prevent damage or destruction by oxidation by free radicals. Bananas are an alternative source of natural antioxidants that can be found every day. Bananas are high in nutrients, low in cholesterol, have high levels of vitamin B6 and vitamin C, and are versatile plants from radix to hesperidium. This study aims to determine the benefits of banana hesperidium as (Musa Paradisiaca L) which has antioxidant activity and can be used as a natural antioxidant gel preparation. Experimental laboratory research using immersion method with 70% ethanol solvent to produce extracts. Antioxidant activity testing using UV-VIS spectrophotometry with DPPH (1,1-Diphenyl-2-picrylhydrazyl) method. Quantitative assay of antioxidant activity using UV-Vis spectroscopy at a wavelength of 516 nm. The test value of the antioxidant activity of banana hesperidium extract (Musa paradisiaca L) at a concentration of 500 ppm obtained a percentage value of 0.77323%, 1000 ppm of 0.66631%, 1500 ppm of 0.56186%, 2000 ppm of 0.48570. n 2500 ppm is 0.38750. %. The lower the IC50 value of a compound, the stronger its antioxidant activity thus it can be concluded that banana hesperidium can be used as an alternative ingredient as a natural antioxidant gel preparation.